The cyclical impact of EU cohesion policy in fast growing EU countries - Christophe Kamps; Nadine Leiner-Killinger; Reiner Martin (Intereconomics, 2009)
Most of the newly acceded central and east European EU countries are among the main beneficiaries of EU Cohesion Policy. The main objective of this policy is to improve the long-term growth and employment prospects of the supported regions, and thereby to support convergence towards higher levels of per capita income. In the short run, however, EU Cohesion Policy may at times amplify macroeconomic challenges for supported countries. In periods of a downturn of the economy it can have a stabilising impact. During periods of unsustainably fast economic growth, however, its short-term demand effects may contribute to internal and/or external macroeconomic imbalances. Economic policymakers should thus ensure that EU Cohesion Policy enhances long-term productivity, while avoiding, in times of overheating, an increased risk of unsustainable developments as a result of the additional demand stimulus from EU Cohesion Policy .
Keywords: 330